Regional distribution of the knowledge based economy in the EU: towards an oligocentric model? - X. Vence-Deza; Manuel González-López (European Regional Science Association (ERSA), 2004)
The emergence of new economic activities is a driving force of economic growth and its geography is clearly controversial. But the Knowledge-Based Economy (K-BE) is something more than new activities, it is also about the ongoing renewal of all economic activities. And this increasing knowledge intensity of every activity could have an effect on the geography of large part of industries. In this paper we aims to contribute to a better understanding of the geography of Knowledge-Based Economy (K-BE), by an empirical examen of its geographic concentration across European regions. To do so we classify economic activities into six sectors according to its knowledge/technology intensity and we analyse its concentration patterns at the EU regional level (nuts 2). The six sectors we set-up are: High, Medium and Low Knowledge Intensive Services and High, Medium and Low Tech Manufacturing. The data has been provided by the REGIO database (Eurostat). At the same time, we also try to capture the regional specialisation patterns. The results regarding concentration show that the higher the knowledge/technology content of the economic activity, the higher its concentration level is. Besides, we found that some services activities (the high knowledge intensive ones), present similar concentration levels than high or medium tech manufacturing. On the other hand, regarding specialisation the most outstanding result is the clear predominance of metropolitan regions in the highest knowledge/technology intensive activities (particularly in the case of services). Altogether, the picture delivered on a whole viewpoint is one where a reinforced oligocentric model remains in Europe, while relativelly reshaping its appearence: southern German regions leading high and medium tech manufacturing and the English Southeast leading high knowledge-intensive services, but sharing all of them its relevance with a peak range of growing state metropolis (particularly capitals) from both northern and southern Europe. Key words: regional concentration,knowledge intensive activities,oligocentric model.
Keywords: 330; regional concentration; knowledge intensive activities; oligocentric model